Sistema de recomendação ubíquo integrando hipermídias baseadas em ontologias para ambientes de aprendizagem - Bezerra, Sidney Danilo Firmino (Universidade Federal Rural do Semi-Árido, 2018)
The purpose of recommendation system is to offer items more relevant to a consumer. The ubiquitous computing enables the integration of computational systems with the interests of the people, in a transparent way, enabling the construction of systems that integrate the fundamentals of ubiquitous computing with the procedures of analysis of the recommended items. In this way, this work aims to develop and evaluate an application that integrates YouTube videos and documents of the Wikipedia the Youubi API through techniques of recommendations of items along with an ontology, using mobile and web client services, in order to facilitate the teaching-learning process for students, using the fundamentals of ubiquitous computing. The application schema will be composed of the Youubi Application Programming Interface (API), MediaWiki API and Youtube API. These elements interact by exchanging information and making it available to users, they are stored in an ontology called PUYW. This ontology was created through the Web Ontology Language. It is responsible for managing student characteristics and metadata for the YouTube and Wikipedia APIs. To achieve this goal, Design Science was used to support general research questions and methods for the solution. In terms of the methods make use of qualitative and quantitative techniques of data collection, through profile questionnaire, TAM questionnaire, and focal group. The results of this work were evaluated by students of a higher education institution using a system containing a component that integrates videos and articles for teaching and learning systems, and an ontology that manages the profile and manipulated items. The results show that the developed system reached the proposed objectives of this work
Keywords: Computação ubíqua; Design science; Educação; Sistema de recomendação; Ontologia; Design science; Education; Ontology; Ubiquitous computing; Recommendation system; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO